FENOMENA TUKAR UANG BARU MENJELANG HARI RAYA PERSEPTIF FIQH MUAMALAH - Zulfan Mahendra Gultom (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
Every human being in his daily life is always associated with buying and selling transactions as an act of fulfilling the needs of life. This is also seen in the phenomenon of exchanging money or buying and selling money before the holiday. In the implementation of buying and selling, the object being traded must be the same between the value exchanged and the goods to be exchanged. However, the practice in the field is the opposite. This research is a qualitative research using the perspective of the sociology of law to see directly a phenomenon related to the pattern of community activities. There are several factors behind the occurrence of money exchange activities before the holiday, including economic factors to maintain and improve living standards through the benefits obtained from exchange services, besides that legal awareness among traders and buyers is still lacking.